The Effect of Providing Deep Breathing Relaxation Techniques on Anxiety Levels in the Elderly at the Elderly Posyandu in South Sangatta Village - Kartini Puspita Sari; Supriadi; Dwi Prihatin Era (Formosa Journal of Science and Technology, 2023)
The aim of this research was to find out whether there was a difference before and after the deep breathing relaxation technique was given and reducing anxiety levels in the elderly at the posyandu for the elderly in South Sangatta village. The type of research used in this research is experimental research. The approach taken uses the one group pretest and post test design technique. The sample size was 21 respondents based on the Slovin formula using an accidental sampling technique. The research instrument used a questionnaire that had been tested for validity and reliability. Then with a Univariate test and a Bivariate test using the Paired T-Test. The results of the study showed that the difference in the mean of the intervention group between anxiety in the elderly before carrying out the deep breathing relaxation technique and anxiety in the elderly after carrying out the deep breathing relaxation technique was 22 and p value 0.000 < 0.05.